An Evaluation of the Psychometric Properties of the Temporal Satisfaction With Life Scale - Guitard, Joline; Jarden, Aaron; Jarden, Rebecca; Lajoie, Denis (Frontiers in Psychology, 2022)
The Temporal Satisfaction with Life Scale measures judgements of life satisfaction using 15 items, according to three temporal dimensions: past, present, and future. However only seven studies have looked at the psychometric properties of the Temporal Satisfaction with Life Scale, and this has been individually across vastly different countries and cultures (Canada, China, Germany, Spain, Switzerland, Turkey, and United-States), and with different populations, such as undergraduate students, adults, and older adults. In addition, these studies have highlighted issues regarding the replicability of the validity of the scale structure and optimal number of items. In this study we use a large international and multicultural sample (n = 6,912) from the International Wellbeing Study and investigate the scale structure of the Temporal Satisfaction with Life Scale, resulting in the recommendation that a shortened 12-item version provides a better model fit compared to the original 15-item version. More in-depth correlates with aspects of wellbeing and illbeing, in relation to past, present, and future life satisfaction, are also presented than have been previously, which found positive correlations between the temporal dimensions of the Temporal Satisfaction with Life Scale and wellbeing, as well as negative correlations with illbeing measures.